2016
DOI: 10.1080/15569543.2016.1235582
|View full text |Cite
|
Sign up to set email alerts
|

The effects ofPermethrinand antioxidant properties ofAllium cepa(onion) on testicles parameters of male rats

Abstract: The aim of this study was to evaluate the effects of Permethrin on the testes of adult Wistar rats, and evaluate the efficacy of Onion juice supplementation. The male rats were divided into five groups: I: control; II: DMSO (0/5 ml); III: Permethrin (35 mg/kg) in 0/5 ml DMSO; IV: Permethrin (35 mg/kg) + Onion (3 ml); V: onion (3 ml). After 60 days, male rats in all groups prepared to evaluate genital organs weights, the Leydig cells culturing and measurement of testosterone hormone level. Permethrin have negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In the current study, evaluating the fertility power, it was found that pregnancy rate in TDOJ and OJ groups increased in comparison with the testicular torsion/detorsion group. In agreement with the results of the present study, khaki et al also reported that the use of onion juice could increase the concentration and motility of sperm and decrease the percentage of sperm with abnormal morphology (16,30,32).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, evaluating the fertility power, it was found that pregnancy rate in TDOJ and OJ groups increased in comparison with the testicular torsion/detorsion group. In agreement with the results of the present study, khaki et al also reported that the use of onion juice could increase the concentration and motility of sperm and decrease the percentage of sperm with abnormal morphology (16,30,32).…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that antioxidant properties of onion juice and its compounds such as phenolic compositions and flavonoids can prevent overproduction of ROS (30). In the same vein, some studies reported that extract of onion could protect the testis tissue against oxidative damages induced by permethrin (16,30). Besides, Ige et al in their study showed that Allium cepa (AC) could protect the testis tissue against cadmium toxicity (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 4 ] Since spermatogenesis takes place in the testis, any chemical agent like permethrin could be destroyed cellular structure and function and leads to infertility. [ 5 ] On the other hand, done studies for confronting these effects were mostly focused on reducing infertility rate and proposing the best way to treatment. Most studies represent a varied range of antioxidants to solving male infertility.…”
mentioning
confidence: 99%